Clinical importance of VEGFC and PD‐L1 co‐expression in lung adenocarcinoma patients - Tingting Qin; Junling Xia; Shaochuan Liu; Jing Wang; Hailin Liu; Yan Zhang; Yanan Jia; Kai Li (Thoracic Cancer)
Abstract Background Vascular endothelial growth factor C (VEGFC), an activator of lymphangiogenesis, is newly identified as an immunomodulator which can regulate the immune system so that tumor cells more easily escape immune surveillance. Evidence has shown programmed cell death‐ligand 1 (PD‐L1) can also suppress the immune response. Nevertheless, the clinical significance of co‐expression of VEGFC and PD‐L1 for predicting outcomes in patients with lung adenocarcinoma has not yet been determined. Methods A total of 114 patients with lung adenocarcinoma who underwent surgeries at Tianjin Medical University Cancer Institute and Hospital between December 2011 and September 2016 were retrospectively reviewed. Tissue specimens were collected for immunohistochemistry of VEGFC and PD‐L1 which were analyzed with an H‐score system. Results In this study, 57 (50.0%) and 47 (41.2%) patients were classified as VEGFC high expression and PD‐L1 high expression. Co‐expression was observed in 33 (28.9%) patients. In addition, a positive correlation was found between VEGFC and PD‐L1 (P = 0.0398, r = 0.1937). In a univariate analysis, both progression‐free survival (PFS) and overall survival (OS) were significantly worse in the VEGFC high expression group and the PD‐L1 high expression group, respectively. Furthermore, VEGFC/PD‐L1 co‐expression showed a worse OS (P = 0.03) and PFS survival (P = 0.01) than the other groups. Conclusions Taken together, these results indicate that VEGFC/PD‐L1 co‐expression can forecast both poor OS and PFS in patients with resected lung adenocarcinoma. Co‐expression of VEGFC and PD‐L1 may serve as a significant prognostic factor for patients with lung adenocarcinoma. Key points VEGFC/PD‐L1 co‐expression forecasts poor survival in patients with resected lung adenocarcinoma. VEGFC/PD‐L1 co‐expression may be used as a prognostic indicator and provide the theoretical possibility to screen the optimal population with a combination of anti‐VEGFC and anti‐PD‐L1 therapy in the clinical treatment.